Gangliocytic Paraganglioma of Duodenum - Vikram Narang; Nitin Behl; Neena Sood; Harpreet Puri (Case Reports in Pathology)
Gangliocytic paragangliomas are rare benign tumors which are usually encountered in the second portion of the duodenum. Histogenesis of these tumors is incompletely understood. Patients usually present with upper gastrointestinal bleeding. The endoscopic features of gangliocytic paraganglioma do not differ from those of other submucosal tumors. Therefore, they can be diagnosed histologically by the presence of epithelioid, spindle, and ganglion cells, which is similar to that observed for paraganglioma. We herein report a case of gangliocytic paraganglioma due to the rarity of the lesion and the characteristic histopathologic findings.